CD8+ T cell/cancer-associated fibroblast ratio stratifies prognostic and predictive responses to immunotherapy across multiple cancer types - Zheng, Xinlong; Jiang, Kan; Xiao, Weijin; Zeng, Dongqiang; Peng, Wenying; Bai, Jing; Chen, Xiaohui; Li, Pansong; Zhang, Longfeng; Zheng, Xiaobin; Miao, Qian; Wang, Haibo; et al. (Frontiers in Immunology, 2022)
Background: Cancer-associated fibroblasts (CAFs) within the tumor microenvironment (TME) are critical for immune suppression by restricting immune cell infiltration in the tumor stromal zones from penetrating tumor islands and changing their function status, particularly for CD8+ T cells. However, assessing and quantifying the impact of CAFs on immune cells and investigating how this impact is related to clinical outcomes, especially the efficacy of immunotherapy, remains unclear. Materials and Methods: The TME was characterized using immunohistochemical (IHC) analysis using a large-scale sample size of gene-expression profiles. The CD8+ T cell/CAF ratio (CFR) association with survival was investigated in TCGA and GEO lung cancer cohorts. The correlation between CFR and immunotherapeutic efficacy was computed in five independent cohorts. The correlation between CFR and objective response rates (ORR) following pembrolizumab monotherapy was investigated in 20 solid tumor types. To facilitate clinical translation, IHC-detected CD8/α-SMA ratio was applied as an immune-therapeutical predictive biomarker in a real-world lung cancer cohort. Results: Compared with normal tissue, CAFs were enriched in cancer tissue, and the amount of CAFs was overwhelmingly higher than that in other immune cells. CAFs are positively correlated with the extent of immune infiltration. A higher CFR was strongly associated with improved survival in lung cancer, melanoma, and urothelial cancer immunotherapy cohorts. Within most cohorts, there was no clear evidence for an association between CFR and PDL1 or tumor mutational burden (TMB). Compared with TMB and PD-L1, a higher correlation coefficient was observed between CFR and the ORR following pembrolizumab monotherapy in 20 solid tumor types (Spearman r = 0.69 vs. 0.44 and 0.21). In a real-world cohort, patients with a high CFR detected by IHC benefited considerably from immunotherapy compared with those with a low CFR (hazard ratio, 0.37; 95% confidence interval, 0.19–0.75; p < 0.001). Conclusions: CFR is a newly-found and simple parameter that can be used for identifying patients unlikely to benefit from immunotherapy. Future studies are needed to confirm this finding.